The governance of water regulators. (OECD studies on water., 2015)
The establishment of dedicated regulatory bodies in charge of regulating water services, whilst being recent, is nevertheless a consistent trend among OECD and non-OECD countries. This report presents a picture as of September 2014 of the governance arrangements, operational modalities and use of regulatory tools across a sample of 34 established water regulators. It relies on the OECD Best Practice Principles for Regulatory Policy: The Governance of Regulators to structure the information collected through a survey exercise. It has been developed in close co-operation with the OECD Network of Economic Regulators (NER). The results from the survey show that the 34 water regulators show generally a high level of adoption of good governance principles and practices. They display functions and powers that are in line with their objectives. Water regulators also show a strong culture of consultation. Other areas, in particular evaluation of regulatory impacts, could be further strengthened.